EFFECT OF PLATELET RICH PLASMA ON REGENERATION OF ACUTE MEDIAN NERVE INJURY : Pharmaceutical Sciences-Medicine - MOZAFFARIAN, KAMRAN; MOSTAFA JAZAYERI SHOOSHTARI, SEYED; JAVAD FARAHANI, MOHAMMAD (International Journal of Life Science and Pharma Research, 2017)
Currently there is a low success rate of function restoration with aid of surgical techniques. Therefore Peripheral nerve repair and healing have gained an increased attention in recent decades; many studies have investigated this subject. There is a clear need for biomedical engineering research to develop novel strategies to improve outcomes following nerve damage. Double-blinded randomized control trial was designed with 10 patients with acute median nerve injuries at wrist who underwent epiperineurorrhaphy with microsurgical technique. 5 cases received outologus platelet rich plasma (PRP) at repair site. Patients were followed up for evaluation of recovery for 1 year. The average recovery percentage of all variants in case group was 70.33% and 67.38% in control group. The average speed of recovery of all variants in case group was 8.16% and 10.21% in control group in aforementioned time interval. Remarkable recovery was found in pinch power, amplitude and distal latency-motor in both group. Majority of variants had better results after PRP injection at repair site but these changes was not remarkable.